PERBANDINGAN WATERFALL MODEL DAN METODE GENERIK DALAM MANAJEMEN PROYEK PERANGKAT LUNAK SISTEM PENGELOLAAN DANA BANTUAN OPERASIONAL SEKOLAH (BOS) (STUDI KASUS: MAN 1 KOTA LHOKSEUMAWE) - Hari Toha Hidayat (Jurusan Teknik Elektro, Universitas Bangka Belitung, 2016)
Making the software is not an easy job. If we are going to make an application then the required expertise in programming. However, mastery in the field of programming is not enough should have knowledge of project management software. Project management is an important part of software development. The research methodology used the case study of the application making the management of school operational funds in MAN 1 Lhokseumawe. Comparison of two methods of design that is between a generic method with the Waterfall model of result whereby the generic has stages that detailed when compared with the Waterfall model of simple and modest. Based on the research conducted in the making of software projects with short time such as within 1 month then it is better to use the method Waterfall design. But if the work over a long period of about one year and applications are built complex and large then you should use a generic method